Numerical Errors Reduction in Transient Simulations with Resistor Applications - Pereira, Thaina Guimaraes [UNESP]; Gennaro, Elmer Mateus; Prado, Afonso Jose Do [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
It has been investigated about the best parameters to simulate transmission lines using a simple numeric model and taking into consideration the stability and numeric precision. In this study, two-phase lines have been used as examples for the application of the proposed model. It has been used phase-mode transformations to simplify the line modeling and two-phase lines have been represented by two independent mode lines. These independent transmission lines can be represented by cascade of circuits with concentrated elements and this representation has been solved using the trapezoidal rule. In previous applications of this association of the mentioned simple model and the trapezoidal rule, it has been detected undesirable oscillations and numeric error when classic cascade π-circuits or T-circuits are applied. Searching for highly reducing these numeric problems and reducing the computational time in transient simulations, damping resistors and sparse matrix techniques are applied. In case of this paper, two different types of damping resistors will be presented. One of these damping resistors is inserted in parallel to the elements that represent longitudinal line parameters. The other damping resistor type is inserted in series to the elements that represent the transversal line parameters.
Keywords: Electromagnetic transient; linear system; numerical simulation; time-domain analysis; transmission line